Care Economy and the Burden of Housewives’ Work in Indonesia - Atnike Nova Sigiro (Yayasan Jurnal Perempuan, 2018)
Social reproduction role by women are mostly unpaid, which are done in the context of social relation within household or family. In the context of macro economy, care work for family are often overlooked, furthermore are often not being considered as productive work that contribute to the economy. This situation bring overburden to women and the lack of appreciation toward care work in Indonesia. This article was written based on a national survey conducted in 2018 in 34 provinces in Indonesia. The survey measured the care work’s burden of housewives, and public perception towards care economy that are run by housewives in Indonesia.